Practical XMPP : unleash the power of XMPP in order to build exciting, real-time, federated applications based on open standards in a secure and highly scalable fashion /: unleash the power of XMPP in order to build exciting, real-time, federated applications based on open standards in a secure and highly scalable fashion. (2016) - Watkin, Lloyd; Koelle, David
No abstract available